1981
DOI: 10.1021/i200013a032
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of reaction of benzyl chloride with sodium acetate/benzoate: phase transfer catalysis in solid-liquid system

Abstract: Kinetics of the reaction of benzyl chloride with solid sodium acetatelbenzoate, catalyzed by a variety of tertiary amines and quaternary ammonium salts as phase transfer catalysts, was studied at 101 O C in a 10 cm i.d. mechanically agitated contactor. The diffusional resistance was unimportant beyond a speed of 1000 rev/min. The reaction was found to occur in the organic phase and was first order in the concentrations of the substrate and the catalyst. Cetyldimethylbenzylammonium chloride was the most efficie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(40 citation statements)
references
References 11 publications
1
39
0
Order By: Relevance
“…First one is the n o n -s o l u b l e s y s t e m ( h e t e r o g e n e o u s solubilization) introduced by Doraiswamy and Naik [21] and other is soluble system (homogeneous solubilization) introduced by Yadav and Sharma [22]. In this work, β-naphthol dissolved in the organic solvent with the addition of quaternary ammonium salt (QBr).…”
Section: Reaction Mechanism and Kinetic Modelmentioning
confidence: 99%
“…First one is the n o n -s o l u b l e s y s t e m ( h e t e r o g e n e o u s solubilization) introduced by Doraiswamy and Naik [21] and other is soluble system (homogeneous solubilization) introduced by Yadav and Sharma [22]. In this work, β-naphthol dissolved in the organic solvent with the addition of quaternary ammonium salt (QBr).…”
Section: Reaction Mechanism and Kinetic Modelmentioning
confidence: 99%
“…While L-L PTC involves heterogeneous reaction between two reagents located in an aqueous, and an organic phase, S-L PTC involves reaction of an anionic reagent in a solid phase (usually a salt) with a reactant located in a continuous organic phase. Yadav and Sharma [5] proposed the first mechanistic and kinetic model of solid-liquid PTC followed by Naik and Doraiswamy [6]. We have carried out the detailed mechanistic and modelling studies for industrially important reactions under S-L PTC conditions [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…For liquid-liquid phase-transfer catalysis (LLPTC), by contrast, the anion reactant in the aqueous phase reacts with a soluble catalyst to form the catalytic intermediate, which then transfers into the organic phase to conduct the intrinsic organic reaction. Yadav and Sharma [3] investigated the kinetics of reaction of benzyl chloride with sodium acetate/benzoate by SLPTC and found that cetyldimethylbenzylammonium chloride was the most efficient catalyst among those studied. Yang and Wu [4] investigated the reaction of dipotassium phthalate with benzyl bromide and concluded that the esterification can be carried out effectively in SLPTC even without water addition; the behaviors of the active intermediate were also reported.…”
Section: Introductionmentioning
confidence: 99%